Thinning Zhang-Suen dan Stentiford untuk Menentukan Ekstraksi Ciri (Minutiae) Sebagai Identifikasi Pola Sidik Jari - Fakhrina, Faiza Alif; Rahmadwati, Rahmadwati; Wijono, Wijono (Majalah Ilmiah Teknologi Elektro; Vol 15 No 2 (2016): (July - December) Majalah Ilmiah Teknologi Elektro, 2016)
Fingerprint is the skin on the palms of the hands and feet that are covered with small ridge lines. Fingerprint pattern belonging to every human is being unique. There are fingerprint on the ridge pattern will not change during human life. Ridge pattern is characteristic of the fingrprint that can be used for biometric identification. Based on fingerprint ridge pattern into four, namely whorl, ulnar loop, radial loop, and arch. Minutiae Extraction (Crossing Number), Core and Delta, Center Point Location can be used for fingerprint pattern recognition. Some of the methods used in the fingerprint pattern recognition is Minutiae Extraction, and Thinning Zhang-Suen and Stentiford. Croosing Number is used for process Minutiae Extraction, example termination and bifurcation. The classification method used Linear Discriminant Analysis. The result fingerprint pattern recognition is system can recognize fingerprint patter as much as 20 images and system can not recognize fingerprint pattern as much as 10 images. Accuracy of fingerprint pattern recognition is 66%.
Keywords: Sidik Jari, Pola Sidik Jari, Ekstraksi Minutiae, Crossing Number, Linear Discriminant Analysis.